Identifying and controlling a multiresistant pseudomonas aeruginosa outbreak in a latin-american cancer centre and its associated risk factors - Jorge Alberto Cortes; Sonia Isabel Cuervo; Ana María Urdaneta; Guillermo Potdevin; Patricia Arroyo; Diana Bermúdez; Adriana Correa; María Virginia Villegas (Brazilian Journal of Infectious Diseases)
Pseudomonas aeruginosa is an important and frightening microorganism for patients suffering from cancer. Multiresistant P. aeruginosa (MRPA) may appear as a consequence of exposure to multiple antibiotics or from a breakdown in infection control practices. This article reports an MRPA outbreak in a cancer treatment centre and the consequent case control study. Mechanical ventilation was identified as being the main risk factor for developing MRPA colonisation or infection; molecular analysis confirmed the outbreak. A multifaceted strategy was adopted, involving reinforcing hand-washing practices, contact isolation, antibiotic restriction and suction devices for mechanically-ventilated patients. MRPA was controlled and the outbreak ended. Such strategy may be effective in controlling MRPS in low-resource environments amongst high risk cancer patients.